Comparison of Crenarchaeal Consortia Inhabiting the Rhizosphere of Diverse Terrestrial Plants with Those in Bulk Soil in Native Environments - Sliwinski, Marek K. (American Society for Microbiology, 2004)
To explore whether the crenarchaeal consortium found in the rhizosphere is distinct from the assemblage of crenarchaeotes inhabiting bulk soil, PCR-single-stranded-conformation polymorphism (PCR-SSCP) profiles were generated for 76 plant samples collected from native environments. Divergent terrestrial plant groups including bryophytes (mosses), lycopods (club mosses), pteridophytes (ferns), gymnosperms (conifers), and angiosperms (seed plants) were collected for this study. Statistical analysis revealed significant differences between rhizosphere and bulk soil PCR-SSCP profiles (Hotelling paired T(2) test, P < 0.0001), suggesting that a distinct crenarchaeal consortium is associated with plants. In general, phylotype richness increased in the rhizosphere compared to the corresponding bulk soil, although the range of this increase was variable. Examples of a major change in rhizosphere (versus bulk soil) PCR-SSCP profiles were detected for all plant groups, suggesting that crenarchaeotes form associations with phylogenetically diverse plants in native environments. In addition, examples of minor to no detectable difference were found for all terrestrial plant groups, suggesting that crenarchaeal associations with plants are mediated by environmental conditions.